Bioremediation of Disposed X-Ray Film For Enzymes Production - Noor Afifah, Fauzi; Siti Hajar, Mohd Rasdi; Makky, Essam A.; Mohd Hasbi, Ab. Rahim (Scholarly Peer Review Publishing System, 2016)
Annually, the production of X-ray films sheets can utilize up to 1000 tons of total silver chemically produced worldwide and being wasted when these films are used. To avoid waste, the biological methods are used to study the effect of disposed X-ray on production of two different types of enzyme by using microbial power. Firstly, production of CMCase enzyme by using disposed X-ray as a carbon source. Secondly, production of nitrate reductase enzyme responsible to catalyse the reduction of silver nitrate inside X-ray film. Both bring the disposed X-ray as a substrate. Different bacterial isolates were used for production of both enzymes and being optimized by using several parameters. The protein and enzyme assay were analysed using optical density measurement. CMCase production found to be optimal in 140 rpm incubator with lactose as carbon source by 1.365±0.026 (U/ml), malt extract as nitrogen source by 0.485±0.028 (U/ml), pH 9.0 by 0.129±0.007 (U/ml), 1.5 g substrate concentration by 0.217±0.007 (U/ml), 2ml inoculum size by 0.143±0.029 (U/ml), and thiamine for vitamin by 0.208±0.041 (U/ml). While nitrate reductase production, the most potent isolates achieved optimum condition in static incubation condition by 1.182±0.000μg/ml, 0.5g substrate concentration by 1.500±0.020μg/ml with 15 days incubation periods in darkness, NaNO3 as nitrogen source by 166.773±0.054μg/ml and pH 3.0 by 0.773±0.001μg/ml. This study proved that the power of most potent isolates successfully used the disposed X-ray as substrate to produce valuable by-products using green technology to reduce environmental pollution.